(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Customer experience is the consequence of association between an association and a customer amid the length of their relationship. This relationship is comprised of three sections: the client venture, the brand contact focuses the client associates with, and the conditions the client encounters amid their great client encounter implies that a person’s understanding amid all purposes of contact coordinates a person’s desire.Social media marketing provides discovery of new content and also builds the link with the customers. Many people use social media to search various products and services to which social media marketing acts as an effective tool.This paper shows the comparative trend in customer experience and social media marketing of Amazon and Flipkart.